국산 신품종 감자의 이화학적, 구조적 및 유변학적 특성 - 최문경(Moonkyeung Choi); 이준구(Jungu Lee); 진용익(Yong-Ik Jin); 장동칠(Dong-Chil Chang); 김미숙(Misook Kim); 이영승(Youngseung Lee); 장윤혁(Yoon Hyuk Chang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
The objective of this study was to evaluate the physicochemical, structural, and rheological properties of new domestic potato cultivars ('Goun', 'Sebong', and 'Jinsun') against the foreign potato cultivar 'Atlantic'. Based on the results obtained from scanning electron micrograph, X-ray, and Fourier transform infrared spectrum analyses, the structural properties of all potato flours were not considerably different. Rapid visco analyzer analyses showed that the setback viscosities of 'Goun', 'Sebong', and 'Jinsun' were significantly lower than that of 'Atlantic'. For steady shear rheological properties, potato flour dispersions showed shear-thinning behaviors (n=0.45~0.49) at $25^{°}C$. Apparent viscosity and consistency index of 'Atlantic' were similar to those of 'Sebong' and 'Jinsun'. For dynamic shear rheological properties, storage modulus (G′) and loss modulus increased, whereas complex viscosity (${η}^*$) was reduced with increasing frequency from 0.63 to 62.8 rad/s. G′ and ${η}^*$ values of 'Jinsun' were significantly higher than those of the other potato cultivars. 본 연구는 국산 신품종 감자인 '고운', '새봉', '진선'의 이화학적, 구조적 및 유변학적 특성을 도입 품종인 '대서'와 비교하여 측정함으로써 신품종 감자의 가공적성 규명과 가공식품 제조를 위한 기초자료를 마련하기 위해 수행되었다. 감자가루의 총전분 함량은 도입 품종인 '대서'에서 73.34%로 유의적으로 가장 높게 나타났다. 품종별 감자가루의 인 함량은 '새봉'에서 2,249.94 ppm으로 가장 높게 나타났다. 신품종 감자가루의 구조분석 결과 전분 입자에 비전분성 물질이 결합 혹은 자유롭게 존재하는 미세구조를 나타내었고, X-선 회절도 분석에서 B형 전분의 결정형 피크를 나타내었다. FT-IR 분석 결과 지문영역에서 품종 간에 차이가 나타나지 않아 '대서'와 신품종 감자의 구조적인 특성에는 차이가 없는 것으로 나타났다. Rapid Visco Analyzer에 의한 페이스팅 특성은 '새봉' 품종의 peak viscosity가 유의적으로 높게 나타났으며, setback viscosity는 신품종 감자(38.67~56.00 cP)가 '대서(72.00 cP)'보다 낮게 나타났다. 정상유동 특성은 '대서'의 점조도 지수와 겉보기 점도가 가장 높게 나타났으며, 동적 점탄 특성에서는 진동수가 증가함에 따라 저장 탄성률(G′)과 손실 탄성률(G″) 값이 증가하는 경향을 나타내었으며, '진선'의 G′, G″과 복소 점도 값이 가장 높게 나타났다.